The moderating role of personal innovativeness in tourists’ intention to use Web 3.0 based on updated information systems success model - Albaom, Mohammed Abdo; Sidi, Fatimah; A. Jabar, Marzanah; Abdullah, Rusli; Ishak, Iskandar; Yunikawati, Nur Anita; Priambodo, Magistyo Purboyo; Nusari, Mohammed Saleh; Ali, Dhakir Abbas (Mary Ann Liebert, 2022)
Rapid technological development has led to an information explosion in the current Web environment. Recently, tourists have become reliant on the Internet as a tool to obtain information about the places they intend to visit. However, due to the overload of information, tourists face many challenges and difficulties in making the right choice. Despite the promise of Web 3.0’s revolutionary solutions to address all of Web 2.0’s shortcomings, there is still a significant gap between currently implemented systems and the useful innovation of future technologies in the tourism industry. This study proposes a theoretical model to examine the role of personal innovativeness in tourists’ intention to use Web 3.0 based on the DeLone and McLean model. Although many attempts were made in prior work to address this issue, most of those studies focused on the evolution of Web 3.0 from the technical side and did not investigate it from the theoretical perspective in different domains in general and tourism in particular. The method of this study was based on a survey questionnaire with 643 participants. SmartPLS version 3.3.3 was used to analyze the study data. The results of this study reveal that information quality, system quality, service quality, social influence, and personal innovativeness had significant effects on tourists’ intention to use Web 3.0, while awareness did not have a significant effect. This study provides further insights, expands our understanding of the study topic, and contributes to this growing research area, and the novel research framework can act as a fundamental theoretical model for future studies in different contexts.